IMPLEMENTASI ETIKA ISLAM DALAM PEMASARAN PRODUK BANK SYARIAH - Putri, Azizah Aprilia; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2025)
Marketing personnel are the main means of connecting the company with consumers or are the spearhead of the company's business. For the banking world which is a profit-oriented business entity, marketing activities are already a main need and have become a must to be carried out, therefore marketers of banking products are required to be creative and innovative in carrying out marketing activities. This study aims to understand the behavior of Islamic bank marketers through the application of Islamic business ethics in marketing Islamic bank products in the city of Parepare. The results of the study show that the marketers of Islamic banks in the city of Parepare have fully implemented sharia values which are part of the concept of Islamic business ethics in their marketing activities. The application of Islamic business ethics to Islamic bank marketers is considered very appropriate. Islamic banks that have quality marketing personnel based on Islamic ethics can build a reputation for the success of Islamic bank development in Parepare